Perspektif Hukum dalam Keterbukaan, Transparansi, Proporsional, dan Penegakan Hukum pada Kontrak Pengadaan Barang dan jasa Pemerintah - Hardiyan, Sandi Pratama (Perspektif Hukum, 2023)
This research examines the legal perspective on openness, transparency, proportionality and law enforcement in contracts for the procurement of government goods and services. Implementing the principles of openness and transparency is key in maintaining a fair and open procurement process. The principle of proportionality plays an important role in balancing government objectives with the rights and obligations of providers of goods and services. The principles of openness and transparency need to be implemented carefully in the process of procuring government goods and services in order to gain public trust. Apart from that, the principle of proportionality in contracts for the procurement of government goods and services needs to be taken into account in order to achieve a balance between the government and providers of goods and services. In the event that a dispute occurs in a contract for the procurement of government goods and services, it can be resolved using 4 methods, namely through contact dispute resolution services, arbitration, construction dispute council, or through court. This research uses legal research methods using a statutory regulation approach and a conceptual approach. This research aims to explore the principles of openness, transparency, the principle of proportionality, and law enforcement of contracts for the procurement of government goods and services from a legal perspective.